An Enhanced Z-Source Switched MLI Capacitor for Integrated Micro-Grid with Advanced Switching Pattern Scheme - Manjunatha, B. M.; Nagaraja Rao, S.; Suresh Kumar, A.; Lakshmi Devi, V.; Rama Mohan, P.; Brahmanandam, K. (Engineering, Technology & Applied Science Research, 2022)
In this paper, the Enhanced Z-Source Switched Capacitor Multi-Level Inverter (EZSC-MLI) is presented, which can generate a greater number of levels and magnitude in output. The proposed MLI has greater recognition due to its low harmonic profile, fewer switching components, compact size, low switch stress, isolated DC supply, high efficiency, and low cost. A high voltage boost factor is achieved by using the Z-Source. The Switched Capacitor module is used for charging all the capacitors to equal voltage magnitude based on a self-balanced scheme. The proposed topology for grid integration requires dual control loops, a primary voltage control loop, and a secondary current control loop. The performance of the proposed 7-level topology for grid integrated systems is verified with multi-carrier advanced modulation schemes and by simulations carried out in Matlab/Simulink.